Comparison of Image Distribution Schemes in a Wireless Presentation System - X. Kok, G.; N. Choong, K. (International Journal of Engineering and Technology, 2018)
We proposed and compared several image distribution schemes for the webviewer scenario in a wireless presentation session. Simulation study showed that by optimizing the image transmission rate, a good tradeoff solution that maximizes the combined weighted video and image quality could be achieved.Â Â